When Matilda shows up: The double-edged impact of women researchers’ media visibility in management science - Béatrice Parguel; Marine Agogué; Julie Gauneau (PLoS ONE, 2026)
Although the proportion of women in academic positions has increased, women researchers continue to receive less media coverage than their counterparts. To examine the implications of this underrepresentation, we investigate how different audiences respond to women researchers’ increased visibility in social sciences dissemination media. We conducted two laboratory experiments, the first with a sample of non-academic individuals (N = 271) and the second with a sample of graduate students (N = 129). Results show that greater visibility of women researchers reduces the gender gap in self-efficacy beliefs between men and women in both populations. It also increases women researchers’ perceived expertise among non-academic participants, but not among graduate students. Among the later, however, heightened visibility is also unexpectedly associated with a decline in the perceived attractiveness of academic careers, but only for men. While our research focuses specifically on women researchers in the field of management science and manipulates media visibility through the relative representation of women and men in a simulated scientific dissemination newsletter, our findings offer broader insights into how media exposure can influence self-efficacy beliefs, perceptions of researchers’ expertise, and the attractiveness of academic careers. Building on these insights, we propose recommendations for researchers, academic institutions, and media organizations engaged in science dissemination.